Proceedings of the 4th International Workshop on Multimedia for Personal Health &Amp; Health Care 2019
DOI: 10.1145/3347444.3356237
|View full text |Cite
|
Sign up to set email alerts
|

Am I Coughing More Than Usual?

Abstract: An increasing number telehealth systems continuously collect selfreported data from patients. Objective and subjective collection of health data facilitates early detection and treatment of chronic conditions, but patient needs in these telehealth contexts are poorly understood. It is for example not clear how to support patients' reflection on their daily self-reported data. Inadequate support can result in fragmented daily health monitoring and poor adherence. This paper contributes 1) a synthesis of the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Despite the benefits of viewing patient-generated data, self-assessed data may be too variable for decision-making. Previous work has shown that it is challenging for patients with COPD to answer subjective questions about breathlessness and coughing [79]. To address this, patients may underreport symptoms unless there are large deviations from their baseline [79].…”
Section: Subjective Data Recorded By Patients Is Challenging For Deci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the benefits of viewing patient-generated data, self-assessed data may be too variable for decision-making. Previous work has shown that it is challenging for patients with COPD to answer subjective questions about breathlessness and coughing [79]. To address this, patients may underreport symptoms unless there are large deviations from their baseline [79].…”
Section: Subjective Data Recorded By Patients Is Challenging For Deci...mentioning
confidence: 99%
“…Previous work has shown that it is challenging for patients with COPD to answer subjective questions about breathlessness and coughing [79]. To address this, patients may underreport symptoms unless there are large deviations from their baseline [79]. Unreliable reporting of symptoms impacts how data are interpreted by HCPs, which means that patients may not receive the care they require.…”
Section: Subjective Data Recorded By Patients Is Challenging For Deci...mentioning
confidence: 99%
“…However, these systems should not relegate patients to passively monitoring data, e.g. without access to the data [15,29], but should encourage mutual understanding between HCPs and patients on the extent and potential use of tracked data [32].…”
Section: Introductionmentioning
confidence: 99%